2022
DOI: 10.1002/lno.12215
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how nutrient limitation and plant traits influence carbon in mangrove‐seagrass coastal ecosystems

Abstract: Mangrove forests and seagrass meadows provide critical ecosystem services, including the accumulation of "blue carbon." Plants' functional traits could influence this blue carbon accumulation. To test for interactions among functional traits and blue carbon accumulation, we conducted a study in connected mangrove-seagrass coastal ecosystems in southeast Florida (USA). We quantified how plants' above-ground traits correlated with sediment nutrient content, and how changes in traits along inland-to-coastal gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…For instance, root structure for mangrove trees has been identified as a trait explaining sedimentary OC (Gillis et al, 2015). Also, traits related to seagrass structural complexity such as above‐ground biomass, below‐ground biomass and leaf area index have been positively correlated with sedimentary OC (Kammann et al, 2022; Samper‐Villarreal et al, 2016), since the highly complex canopies enhances the attenuation of the flow and the deposition of the suspended particulate organic matter in the water column, while below‐ground biomass limits its resuspension (Dahl et al, 2018). In salt marshes, plant traits can explain a high proportion of the variation shown in carbon stocks (37% in salt marshes in the United Kingdom; Ford et al, 2019).…”
Section: Trait Mechanisms Driving Blue Carbon Potentialmentioning
confidence: 99%
“…For instance, root structure for mangrove trees has been identified as a trait explaining sedimentary OC (Gillis et al, 2015). Also, traits related to seagrass structural complexity such as above‐ground biomass, below‐ground biomass and leaf area index have been positively correlated with sedimentary OC (Kammann et al, 2022; Samper‐Villarreal et al, 2016), since the highly complex canopies enhances the attenuation of the flow and the deposition of the suspended particulate organic matter in the water column, while below‐ground biomass limits its resuspension (Dahl et al, 2018). In salt marshes, plant traits can explain a high proportion of the variation shown in carbon stocks (37% in salt marshes in the United Kingdom; Ford et al, 2019).…”
Section: Trait Mechanisms Driving Blue Carbon Potentialmentioning
confidence: 99%
“…Several studies in this special issue address the origin, variability, and drivers of the sediment carbon pool and fluxes. Samper-Villarreal et al (2022) found that sediment organic carbon storage in tropical seagrass meadows can be independent of species composition, while Kammann et al (2022) demonstrated that vegetation traits and nutrient availability modify organic carbon sequestration in other seagrass and mangrove sediments. Krause et al (2022) showed that a large fraction of sediment organic carbon in seagrass and saltmarsh ecosystems originates from adjacent ecosystems rather than through in situ production.…”
mentioning
confidence: 99%
“…Mangrove, seagrass, coral (Adame et al, 2012;Briand et al, 2015;Hernández et al, 2022;León-Pérez et al, 2023;Middelburg et al, 1996;Signa et al, 2017) Mangrove, seagrass (Asplund et al, 2021;Dahl et al, 2022;Hidayah et al, 2022;Kammann et al, 2022;A. K. Mishra et al, 2023;Sullivan et al, 2021;Walton et al, 2014) Mangrove, coral (Keyes et al, 2019) Mangrove (Agraz-Hernández et al, 2018;Analuddin et al, 2021;Feller et al, 2015;Gillis et al, 2016;Moroyoqui-Rojo et al, 2015;Vaiphasa et al, 2007;Williams et al, 2013) Seagrass (Apostolaki et al, 2012;…”
Section: Carbon Stocks and Nutrientsunclassified
“…As the organic matter load from mangroves is context and site-dependent (Signa et al, 2017), they may serve as subsidiaries of organic matter and nutrients to seagrass and corals (Adame et al, 2012;Briand et al, 2015;Mishra et al, 2023;Sullivan et al, 2021), while the input of seagrass material also supports mangrove production (Walton et al, 2014). Furthermore, a study on a connected mangrove-seagrass system concluded that higher sediment nutrient concentrations benefit seagrass density and coverage, and consequently their carbon accumulation potential (Kammann et al, 2022). On the other hand, high phosphorus concentrations in soil can decrease mangrove root complexity (as phosphorus is readily available), which negatively affects carbon storage (Kammann et al, 2022).…”
Section: Nutrient Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation